Analisis Bahasa Slang pada Komunitas Windah Basudara di Aplikasi X - Nadia Safa; Yolanda Ghina Aulia; Ahmad Deas Syahputra; Awang Yanuar Islami (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This research aims to identify the forms of slang used by the Windah Basudara Community on application X, the functions of slang usage on application X, and also the reasons why slang is more frequently used by the Windah Basudara Community on application X currently. This research uses slang language analysis as the subject and the Windah Basudara Community as the object. This research uses a descriptive qualitative method. The topic of this research is the use of slang language on application X. The data collection methods used in this research are reading, note-taking, and screenshots. To achieve the research objectives, the researcher analyzes the slang language used by the Windah Basudara Community on application X. Data analysis is conducted by observing the language in the Windah Basudara Community, focusing on the use of language that does not conform to KBBI, and seeking the meaning of the language used.